From source water to drinking water : workshop summary - Reiter, Lawrence W.; Falk, Henry; Groat, Charles G.; Coussens, Christine (Online access: National Academy of Sciences National Academies Press., 2004)
The reliable provision of safe drinking water in the United States and other countries represents one of the outstanding public health accomplishments of the past century. This capability derived from major and mutually reinforcing efforts by researchers in public health, engineers, and governments at all levels, municipal, state, and federal to put the necessary infrastructure in place, develop standards and regulations, and implement them effectively. As a result, the majority of people in the United States today enjoy an unprecedented level of protection and safety in the drinking water they consume. However, the system that was put in place for delivering safe and adequate supplies of drinking water has been in existence for more than 100 years. During the ensuing century, the United States has experienced a surge in population growth, which is projected to increase until 2050; a shift of population from densely populated urban areas to sparsely populated rural areas; and greater demands on water for multiple needs such as recreation, drinking water consumption, industrial use, and agricultural use. All of these needs have resulted in additional pressure on our waterways and will likely affect our ability to supply adequate water in the future, according to some workshop participants. This workshop, which was sponsored by the Institute of Medicine, s Roundtable on Environmental Health Sciences, Research, and Medicine, provided an opportunity to look at the progress achieved since the passage of the Safe Drinking Water Act and the Clean Water Act. It looked at previous and future challenges that will continue in environmental health.